2019
DOI: 10.1021/acs.jpcc.8b10999
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insight into the Nature of Dopants in Graphene Derivatives Influencing Electromagnetic Interference Shielding Properties in Hybrid Polymer Nanocomposites

Abstract: The recent surge in the usage of electronics has led to a new kind of problem; electromagnetic interference which necessitates finding alternate materials that offer ease of processing, design flexibility, light weight, and ease of embedding and integrating with the existing systems in place as shields to protect the precise electronic circuitry. Herein, lightweight polycarbonate (PC)-based nanocomposites using doped graphene derivatives and multiwalled carbon nanotubes (MWCNT) has been explored for effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
51
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 53 publications
0
51
0
Order By: Relevance
“…). FeNi alloy exhibits excellent initial permeability, relative permeability, as well as low coercivity and repeated magnetization loss, and shows great potentials in EMI shielding applications [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…). FeNi alloy exhibits excellent initial permeability, relative permeability, as well as low coercivity and repeated magnetization loss, and shows great potentials in EMI shielding applications [ 34 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fe 3 O 4 has a bandgap of 2.51-3.01 eV 13 , while MoS 2 has a bandgap of 1.23 eV 14 . Considering the multilayered assembly, the ac electrical conductivity showed a frequency-independent plateau at lower frequency following the universal power-law fitting as per equation 1 39,42 .…”
Section: Electrical Conductivity In the Multilayered Assemblymentioning
confidence: 97%
“…It was observed that the MWCNTs worked in tandem with rGO-Fe 3 O 4 and rGO-Gd 2 O 3 , contributing to shielding effectiveness values of 28 and 33 dB, respectively. [151] The authors studied the effect of dopants on shielding effectiveness. Three-dimensional Fe 3 O 4 -decorated CNTs/rGO foam/epoxy was fabricated to improve the interface polarization owing to the large interfacial contact between the multiple phases; hence, improved shielding effectiveness was achieved.…”
Section: Metal/carbon/polymer Compositesmentioning
confidence: 99%